Avaliação da orientação empreendedora social: uma nova perspectiva segundo o modelo de maturidade - Carvalho, Mauricio Nunes Macedo de (Universidade do Vale do Rio dos Sinos, 2020)
Social entrepreneurship is seen as a process of creating social and economic value. An alternative perspective of social entrepreneurship is defined in relation to the individual social entrepreneur, who acts as an agent of social change who, through entrepreneurial behavior, creates solutions to social problems. Attempts to conceptualize and operationalize Social Entrepreneurship (SE) focus efforts on what social entrepreneurs do; however, research that seeks to capture how entrepreneurial actions are linked to results remains scarce. As a way of contributing to the advancement of research in this field, the present study aimed to propose a model for the Assessment of Maturity of Social Entrepreneurial Orientation (SEO). To achieve the results, the research has an exploratory character, whose qualitative approach sought to investigate a multiple case study, through in-depth semistructured interviews with fifteen social entrepreneurs, located in RS. The survey results elucidated five different stages of maturity of social entrepreneurial orientation, highlighting its triggers for development and assigning a global assessment of the maturity of OES to social entrepreneurs. This research is limited to the South-Brazilian context, in the same way, its results captured a specific moment of development of the social entrepreneur, regarding his entrepreneurial orientation, in this sense, replications in other cultural contexts and longitudinal studies would enrich the debate about the theme. The proposed evaluation model sought to be unique in the context of measuring Social Entrepreneurial Orientation, by adopting a perspective of maturity stages that sought to qualitatively describe the main characteristics that concern the orientation adopted by social entrepreneurs, in different stages of development, becoming useful both in the academic and managerial fields.
Keywords: Orientação empreendedora social; Modelo de maturidade; Empreendedorismo social; Social entrepreneurial orientation; Maturity model; Social entrepreneurship; ACCNPQ::Engenharias::Engenharia de Produção